COMPATIBILITY OF PYRETHROID AND DIFFERENT CONCENTRATIONS OF NEEM SEED EXTRACT ON PARASITOID TRICHOGRAMMA CHILONIS (ISHII) (HYMENOPTERA: TRICHOGRAMMATIDAE) UNDER LABORATORY CONDITIONS - Khan, M. H.; Sarwar, M.; Farid, A.; Syed, F. (The Nucleus, 2010)
The parasitoid, Trichogramma chilonis (Ishii) (Hymenoptera: Trichogrammatidae) is an important egg parasitoid, reported to reduce the lepidopteron pest populations considerably and often released agumentatively in integrated pest management (IPM) programs of crops and vegetables. Studies on the effect of pyrethroid (ripcard 0.5%) and different concentrations of neem (Azadirachta indica) seed extract on T. chilonis were conducted. Among different concentrations of neem seed extract (4, 2, 1, 0.5 and 0.25%), the highest mortality (68.29%) of Trichogramma was recorded with 4% neem seed extract and lowest (35.83%) with 0.25% neem seed extract. Overall, the highest mortality (97.52%) of Trichogramma was recorded with ripcard. Emergence time was non significantly different in all treatments of neem seed extract but was significantly different from ripcard where the emergence time was 9.75 days. Longevity and sex ratio was also non significantly different in all treatments of neem seed extract. It can be concluded that neem seed extract upto 4% concentration can be included in IPM to protect T. chilonis as biological control agent.